2011
DOI: 10.1177/1933719111411728
|View full text |Cite
|
Sign up to set email alerts
|

Multiparity Causes Uncoordinated Activity of Pelvic- and Perineal-Striated Muscles and Urodynamic Changes in Rabbits

Abstract: Temporal and coordinated activation of pelvic- (pubococcygeous) and perineal- (bulbospongiosus and ischiocavernosus) striated muscles occurs during micturition in female rabbits. We have hypothesized that the coordinated activation of pelvic and perineal muscles is modified during the micturition of young multiparous rabbits. Young virgin and multiparous female chinchilla rabbits were used to simultaneously record cystometrograms and electromyograms of the pubococcygeous, ischocavernosus, and bulbospongiosus m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 34 publications
6
37
0
Order By: Relevance
“…16 In addition, similar to humans, a temporal coordination between the pelvic and perineal muscles during micturition and parity associated modification of functional properties of these muscles was also reported in the rabbit. 17 Our pharmacological studies confirm previous observations that UP is under the influence of smooth as well as striated muscles. 14,18,19 To our knowledge the novel aspect of our study is that not 1 but 2 skeletal muscle components, ie the RHB and PRM, contribute to urethral pressure.…”
Section: Discussionsupporting
confidence: 90%
“…16 In addition, similar to humans, a temporal coordination between the pelvic and perineal muscles during micturition and parity associated modification of functional properties of these muscles was also reported in the rabbit. 17 Our pharmacological studies confirm previous observations that UP is under the influence of smooth as well as striated muscles. 14,18,19 To our knowledge the novel aspect of our study is that not 1 but 2 skeletal muscle components, ie the RHB and PRM, contribute to urethral pressure.…”
Section: Discussionsupporting
confidence: 90%
“…Apart from the rat, the most used species to attain basic knowledge regarding the structure‐function relationship of pelvic floor muscles, the female rabbit is an alternative model organism since their muscles are well‐developed and accessible for morphometric and functional analyses. Previous studies in this model have reported that multiparity alters the reflex activity of the Pc and Bs muscles during the induced micturition . Besides plausible neurological alterations, it is clear that multiparity affects the morphometry of these muscles and reduces their contractile force .…”
Section: Introductionmentioning
confidence: 72%
“…Pelvic and perineal skeletal muscles play important roles in reproductive and excretory functions . Women are more prone than men to suffer pelvic floor dysfunctions, which is clearly linked to factors such as age, menopause, and the number of childbirths, among others .…”
Section: Introductionmentioning
confidence: 99%
“…Multiparity (4 consecutive vaginal deliveries) causes uncoordinated activity of pelvic and perineal muscles, and modifies urodynamics ( Fig. 7; Martínez-Gómez et al, 2011). All multiparous rabbits included in that study had a pattern of muscle activity different than that of the virgin rabbits.…”
Section: Pelvic and Perineal Muscles In Virgin And Multiparous Rabbitsmentioning
confidence: 97%
“…al., 2008). Also, both women and female rabbits have been reported that during childbirth damage is produced of the pelvic floor muscles and nerves, leading to cause uncoordinated activity of pelvic and perineal muscles, modifying the micturition and producing postpartum urinary incontinence (Deindl et al, 1998;Haylen, 2009;Martínez-Gómez et al, 2011).…”
Section: Pelvic-and Perineal-muscle Activities During Micturitionmentioning
confidence: 99%